Hierarchical Assembly of Surface Modified Silk Fibroin Biomass into Micro‐, and Milli‐Metric Hybrid Aerogels with Core‐Shell, Janus, and Composite Configurations for Rapid Removal of Water Pollutants. Issue 5 (18th January 2021) - Bruder, Valentin; Ludwig, Tim; Opitz, Stephan; Christoffels, Ronja; Fischer, Thomas; Maleki, Hajar
Abstract: Multifunctional aerogels, with intriguing micro‐morphologies and macroscopic sizes, are fabricated for the first time from silk fibroin (SF) biopolymer extracted from Bombyx mori silkworm cocoon to optimize the adsorption performances of heavy metal ions and soluble organic pollutants. By a synergistic combination of approaches such as surface‐modification of SF with polyethyleneimine (PEI) and its hierarchical cryo‐assembly with graphene oxide into various macrostructures, namely core‐shell, composite, and Janus, series of millimetric aerogels (2–3 mm) with interesting center divergent honeycomb micro‐morphologies are prepared. In addition, cryo‐assembly assisted electro‐spraying of SF‐PEI led to obtaining micro‐aerogels (74 µm), possessing a wrinkled surface morphology with a high surface area. The aerogel beads exhibit superior adsorption capacities for Cu 2+ (186.7 mg g −1, in 240 min) with a regeneration potential, but also for anionic dyes, for example, methylene orange (811.3 mg g −1 ) and organic solvents (1138 g g −1 % for chloroform). The large adsorption capacities and fast adsorption kinetics of cations obtained by these aerogels are attributed to their impressive micro‐morphologies and small geometries, enabling rapid diffusion and cations uptake. Therefore, the sustainability, biodegradability, ease of fabrications, rapid, and reusable adsorption performance make aerogel beads of this study highly potent for multipollutant adsorption. Abstract : In this study, various hybrid micro, and millimetric silk fibroin‐based aerogels with interesting micro‐morphologies are fabricated through synergistic combination of surface modification, and cryo‐assembly approaches for removal of water‐based pollutants.